Sub‐THz Phase Shifters Enabled by Photoconductive Single‐Walled Carbon Nanotube Layers - Serguei Smirnov; Aleksandra Przewłoka; Aleksandra Krajewska; Dmitry Zykov; Petr Demchenko; Joachim Oberhammer; Mikhail Khodzitsky; Igor Nefedov; Dmitri Lioubtchenko (Advanced Photonics Research, 2023)
Materials with tunable dielectric properties are highly relevant for terahertz (THz) applications. Herein, the tuning of the dielectric response of single‐walled carbon nanotube layers by light illumination is studied for applications to THz phase shifters. The dependence of the length of individual nanotubes on the THz photoconductivity of the network is experimentally investigated in the frequency range of 0.2–1 THz by time‐domain spectroscopy (TDS). The effective conductivity of the networks is described by a theoretical model that fits the measured dielectric function. Terahertz phase shifters are realized with the carbon nanotube layers as the optically tunable element deposited on the wall of rectangular dielectric waveguides. The phase of the electromagnetic wave propagating in the waveguide is shown to be tunable by illuminating the nanotubes. A linear phase shift with the frequency is measured between 75 and 500 GHz with a low change in amplitude due to the illumination.